Book trailer - Maswi, Nur Syiffa; Muhammad, Nursyakirah; Mustafa, Fasihah Husna; Zalzala, Nur Ain Najwa; Arif, Zuraidah (Universiti Teknologi MARA, Kedah, 2019)
The advance of technology has brought many advantages to the library. Yet, at the same time it also put the library in pain due to the changing of interest given by users which more preferred in using social media or on consume resources found in the internet. Thousands of library collections need to be use to the optimum level. Often library faced pain in encouraging their users to read. The society is often no interest in read especially young generation. Society need to search, access and use library collections to the optimum level. Therefore, the society will gain benefit from information and knowledge lies behind it. In 2014 the average of book read by Malaysian are 15 books a year. Thou, its increased as 750 percent compare to the study in 2005 it still not enough to say we have a reading society. The average of 15 book per year is equal to only 0.04 a day! The important of reading is widely discussed. Our Minister of Education, Dr Maszlee Malik often mention we need to established natural reading habit among the community. To support the aspiration, library is supposing to be the first place and or body that cultivate the reading habits among Malaysian. As one of the five laws of library science by Ranganathan stated ‘book are for use’. Library need to ensure the collections are used by its user. In order to seed the interest of a particular title provided by the library, we proposed a promotional tool called ‘Book Trailer’. A book trailer is a helpful marketing tool to promote books. Adapted from the term movie trailer, a book trailer is a short promotional video distributed across multiple platform (e.g. social media). The purpose is to help in increasing online presence and reach a wider audience in stimulating format. The objective is to encourage user to use library collections and to increase user reading interest. The uniqueness of ‘book trailer’ are its work as new promotional tools that work across digital platform.